2009
DOI: 10.1002/zoo.20262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inbreeding on reproductive success, performance, litter size, and survival in captive red wolves (Canis rufus)

Abstract: Captive-breeding programs have been widely used in the conservation of imperiled species, but the effects of inbreeding, frequently expressed in traits related to fitness, are nearly unavoidable in small populations with few founders. Following its planned extirpation in the wild, the endangered red wolf (Canis rufus) was preserved in captivity with just 14 founders. In this study, we evaluated the captive red wolf population for relationships between inbreeding and reproductive performance and fitness. Over 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…A previous study investigated changes in age structure in the captive red wolf population and how those changes affected the population's reproductive potential (Lockyear et al 2009). However, the accuracy of the data set used in the previous study has been questioned (Rabon and Waddell 2010), and relatively few results of the effects of age on reproduction are similar between the two studies. For example, Lockyear et al (2009) reported that reproductive success was negatively correlated only with female age.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study investigated changes in age structure in the captive red wolf population and how those changes affected the population's reproductive potential (Lockyear et al 2009). However, the accuracy of the data set used in the previous study has been questioned (Rabon and Waddell 2010), and relatively few results of the effects of age on reproduction are similar between the two studies. For example, Lockyear et al (2009) reported that reproductive success was negatively correlated only with female age.…”
Section: Discussionmentioning
confidence: 96%
“…As part of a larger study of traits that affect reproduction (e.g., Rabon and Waddell 2010), I examined longitudinal reproductive events of captive red wolves to determine whether parental age, reproductive experience (i.e., prior sexual experience and prior reproductive success), and parental rearing type were factors in the production of offspring. I also examined longitudinal reproductive events to test the relationships between the parental age and reproductive experience of adult males and females and the following measures of reproductive fitness: litter size; litter rearing type; sex ratio of the litter; viability of offspring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model could also be applied to cases where even if captive populations increased in size, they remain initially small for several generations; see for instance, the ex-situ conservation of the Mauritius Kestrel (Falco punctatus) (Jones et al 1995), the Red Wolf (Canis rufus) (Rabon and Waddell 2010) or the Puerto Rican Crested Toad (Peltophryne lemur) (Beauclerc et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding comes with a very high price with respect to the soundness of the reproductive system. This can be manifested in sperm quality (Roldan et al, 1998;Gomendio et al, 2000;Ruiz-Lopez et al, 2010) and in the outcome in term of litter size and survival (Rabon & Waddell, 2010). Once proper sample of sufficiently good quality is in hand, there are several options for its preservation.…”
Section: The Malementioning
confidence: 99%